One-dimensional Site Response Analysis and Liquefaction Evaluation of Can Tho City, Vietnam - Nguyen, T. K.; Nguyen, V. Q. (Engineering, Technology & Applied Science Research, 2022)
Can Tho is the biggest city in the Mekong River Delta, one of the five national central cities in Vietnam. However, it has not been studied regarding seismic hazard estimation. For this purpose, one-dimensional nonlinear site response analysis of this city was performed in this paper. The measured in-situ profiles and corresponding geotechnical site investigation and laboratory test data were utilized to develop the site model for site-specific ground response analysis. A suite of earthquake records compatible with the Vietnam rock design spectrum (TCVN 9386:2012) was used as input ground motions at the bedrock. The results show that Peak Ground Acceleration (PGA) increases from the bedrock to the surface. Maximum PGA is 0.083g for O Mon district (P1) and 0.073g for Cai Rang district (P2). The maximum shear strain is reported to be 0.35% for P1 and 0.45% for P2. The recommended amplification factors are 1.7 for P1 and 1.9 for P2. Even though Can Tho city is composed of soft layers, liquefaction is unlikely to occur.